A 3D nearfield vibration model for simultaneous blasting of multiple holes in the sedimentary rock formation. - Behera S.; Dey K. (My University, 2025)
Blasting is the most common excavation techniques for sedimentary rocks especially for sandstone. However, blasting process leads to unwanted breakage in the rock beyond the desired perimeter of excavation and such breakage is called blast-induced rock damage or ‘backbreak’. In surface blasting, ‘backbreak’ impacts on bench stability, excavator operation and drilling in the new face. However, prior estimation of extent of rock breakage zone can provide an idea to formulate the blast design to control the backbreak. In the estimation of blast-induced damage zones, vibration-based prediction techniques are one of the popular choices due to their easy applicability in varying geotechnical conditions. The existing vibration-based models are mostly one dimensional and estimate the damage zone only for the single blasthole. However, practically more than one blast holes are blasted to match the production requirement. Sometimes due to improper delay sequence or by using detonating fuse as surface connection, more than one blastholes are blasted simultaneously. Thus, in this study, a damage estimation model is developed based on vibration theory, which can estimate the damage zone generated due to the blasting of multiple holes simultaneously. This model is a three-dimensional model, which considers the position of the blast holes, charges and point of damage in a 3D space. The model is tested in sandstone rock through four numbers of single row multiple holes blastrounds. It is found that the model is predicting damage zone with an accuracy of ± 12%. © 2023 Elsevier Ltd